The Anatomy of Executive Aggrandizement in Political Contestation: A Threat to the Principles of Democratic Elections - Dewi Sulastri; Abu Sanmas; Rena Zulfaidah (Fakultas Syariah IAIN Langsa, 2026)
A democratic constitutional system guarantees the existence of checks and balances, the independence of state institutions, and electoral integrity as mechanisms to prevent the concentration of executive power. However, the reality in Indonesia demonstrates a pattern of executive aggrandizement, a gradual expansion of executive authority achieved through the weakening of legislative oversight, judicial independence, and bureaucratic neutrality while utilizing legal instruments that appear constitutionally legitimate. This study aims to analyze the anatomy of executive aggrandizement and its implications for electoral integrity in Indonesia. The research employs a normative-qualitative legal research method using both statutory and conceptual approaches. Data were collected through a literature review of legislation, Constitutional Court decisions, and relevant scholarly works, and were analyzed using content analysis and legal hermeneutics. The findings reveal that the expansion of executive power has been facilitated through the instrumentalization of legal regulations, the bureaucracy, the state budget, and social assistance programs, thereby creating an unlevel playing field in political competition. The study further finds evidence of judicial capture, which has shifted the principle of the rule of law toward rule by law. This transformation has undermined judicial independence, weakened constitutional oversight mechanisms, and substantially diminished the integrity of elections in Indonesia.